∀x,y∈V ( c(x,y) ⇒ c(y,x) ) ∧ ∀x,y,z∈V ( c(x,y) ∨ c(y,z) ∨ c(z,x) ) ⇒ ∀w∈V ∃x,y,z∈V ( c(x,y) ∧ c(y,z) ∧ c(z,x) ∧ x ≠ y ∧ y ≠ z ∧ z ≠ x ) ∨ ∃x,y,z,w,u ∈V ∀t∈V ( t = x ∨ t = y ∨ t = z ∨ t = u ⋁ t = w ), where c : V^2→Bool.
If ∀x,y∈V ( c(x,y) ⇒ c(y,x) ) ∧ ∀x,y,z∈V ( c(x,y) ∨ c(y,z) ∨ c(z,x) ):
If ¬∀w∈V ∃x,y,z∈V ( c(x,y) ∧ c(y,z) ∧ c(z,x) ∧ x ≠ y ∧ y ≠ z ∧ z ≠ x ):
∀x,y,z∈V ( c(x,y) ∨ c(y,z) ∨ c(z,x) )
∀x,y,z∈V ( ¬c(x,y) ∧ ¬c(y,z) ⇒ c(z,x) )
∃w∈V ∀ x,y,z∈V ( c(x,y) ∧ c(y,z) ∧ c(z,x) ⇒ ¬( x ≠ y ∧ y ≠ z ∧ z ≠ x ) )